(untitled) (Research, Society and Development, 2022)
Objective: to identify the risks and prevention measures for nursing professionals as a source of minimizing accidents and biological contamination, in their work environment, especially in hospitals, since the contact with patients is more direct. Method: The article was produced through a study of basic nature with exploratory descriptive objectives, being used the following databases: SCIELO, LILACS, PUBMED, BVS BRASIL, MEDLINE, BDENF-NURSING and legislation and regulatory standards relevant to Biosafety. Performed - time cut of 06 years, 2016 to 2021, with inclusion criteria articles in English, Portuguese and Spanish. Thus, from the content analysis, preceded by rigorous reading, the approaches related to Biosafety were elected. Results: From the approach of Biosafety its risks and prevention measures for nursing professionals, among the 15 articles selected, it can be seen that even given the importance still there is little material on the proposed theme, The importance of discussing the proposed theme in order to influence the nursing professional to reflect on their care practice is well known. Final Considerations: The research showed that a reflection on how to act within the precepts of Biosafety is indispensable. Having access to knowledge of this subject in training courses and training of nursing professionals aims to achieve an increasingly safe practice, given that the number of research on this subject is reduced.